2014
DOI: 10.1111/ctr.12365
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CT‐based measured renal volumes and nuclear‐renography‐based split renal function in living kidney donors. Clinical diagnostic utility and practice patterns

Abstract: CT-based volume measurements in living donor imaging have sufficient correlation with nuclear-based SRF. Selective use of nuclear-scan-based SRF allows careful selection for donor nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…Several studies have previously compared CT‐based techniques with nuclear renography to estimate split kidney function and have shown a high correlation between results, suggesting the feasibility of using CT techniques in this fashion . The two most common types of CT‐based studies are CT volumetry and CT‐GFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have previously compared CT‐based techniques with nuclear renography to estimate split kidney function and have shown a high correlation between results, suggesting the feasibility of using CT techniques in this fashion . The two most common types of CT‐based studies are CT volumetry and CT‐GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have calculated split kidney function using algorithms that quantify and compare kidney enhancement as a function of time after intravenous contrast injection . CT‐based studies have shown a high level of concordance with nuclear renography for determining split kidney function and suggest the feasibility of performing a comprehensive evaluation of live donor candidates using solely CT …”
Section: Introductionmentioning
confidence: 99%
“…addressed the clinical impact of split renal volume (SRV) calculated on the basis of the findings of computed tomography (CT) used to evaluate renal function in patients with renal cell cancer who underwent partial nephrectomy . Previous studies have shown the correlation between renal parenchymal volume determined by CT‐based renal volumetry and loss of estimated glomerular filtration rate, and other studies of living kidney donors have compared the findings of CT‐based renal volumetry and those of nuclear renal scans . On the basis of the results of these studies, the present study shows the possible usefulness of CT‐based volumetry along with nuclear renal scans for estimating split renal functions after nephron‐sparing surgery.…”
mentioning
confidence: 74%
“…According to these reports, there was a significant correlation between mean percent RPV loss and the mean percent eGFR loss ( r = 0.52–0.79). However, although several reports have compared CT‐based volumetry with nuclear renal scan in living kidney donors, there is no such report for nephron‐sparing surgery . As nuclear renal scans provide more accurate information about functional renal parenchyma, it is noteworthy that a stronger significant correlation was found between CT‐based volumetry and nuclear renal scan.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have compared SRV estimated by CT datasets with SRF estimated by nuclear renal scan in living kidney donors for renal transplantation . These studies have shown a significant correlation between SRF and SRV estimated by the two methods ( r = 0.46–0.93).…”
Section: Introductionmentioning
confidence: 99%